2005
DOI: 10.1007/s10439-005-1738-6
|View full text |Cite
|
Sign up to set email alerts
|

Driving Gastric Electrical Activity with Electrical Stimulation

Abstract: Gastric electrical stimulation (GES) therapy is generating a lot of interest, but it is still investigational. Its efficacy in driving gastric electrical activity and improving motility, and the ideal frequency for bringing this about are still controversial. In this study, a rule-based computer model of tissue electrical response to stimulation was developed to examine the interaction between tissue electrical refractoriness and the onset of tissue activation. The results were compared to response to GES in 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Placement of transmucosal electrodes as described here carries a small risk of bleeding and infection at the implantation site, i.e., the usual risks associated with standard endoscopy. In patients without a PEG, similar temporary stimulation can be achieved by placing electrodes at laparoscopy [36] and analytical method can be used to a limited extent [38].…”
Section: Discussionmentioning
confidence: 99%
“…Placement of transmucosal electrodes as described here carries a small risk of bleeding and infection at the implantation site, i.e., the usual risks associated with standard endoscopy. In patients without a PEG, similar temporary stimulation can be achieved by placing electrodes at laparoscopy [36] and analytical method can be used to a limited extent [38].…”
Section: Discussionmentioning
confidence: 99%
“…40 Another study in dogs demonstrated that one can entrain the gastric slow wave and vary their frequencies between two and nine cycles per minute from the normal five per minute normally seen in dogs. 41 Based on these animal studies demonstrating inhibition of gastric contractions and delayed gastric emptying, temporary pacing was evaluated in normal human volunteers. Retrograde pacing with a mucosal electrode placed endoscopically on the greater curvature of the stomach 5 cm above the pyolorus was performed in 12 normal volunteers.…”
Section: Gastric Pacing With Long Pulse Width and Low Frequency For Omentioning
confidence: 99%
“…13,14 Gastric electrical stimulation Implantable gastric stimulation is a less invasive bariatric procedure which utilizes gastric electrical stimulation (GES). [15][16][17] Three techniques have been commonly employed for electrically stimulating the stomach: gastric pacing, 15,18 low-energy high-frequency stimulation 19 and neural GES (NGES). [20][21][22] In gastric pacing, which can be regarded as a lowenergy, low-frequency stimulation technique, the stomach is stimulated at or slightly above its natural electrophysiological frequency, entraining gastric electrical activity also known as Ôslow wavesÕ.…”
Section: Obesity and Available Treatmentsmentioning
confidence: 99%
“…Implantable gastric stimulation is a less invasive bariatric procedure which utilizes gastric electrical stimulation (GES) 15–17 . Three techniques have been commonly employed for electrically stimulating the stomach: gastric pacing, 15,18 low‐energy high‐frequency stimulation 19 and neural GES (NGES) 20–22 …”
Section: Introductionmentioning
confidence: 99%